A centralidade intraurbana em Cuiabá - Borges, Rhafael da Costa (2013)
The present research analyzes the issues of intra-urban centrality, focusing on processes of centralization and decentralization, was elected as the object of study the different centralities intraurbanas Cuiabá city, aiming at analyzing the socio-spatial dynamics of (re) production of the various centralities in your space intraurban and specific objectives: to study the processes of centralization and decentralization occurring in urban areas; research and discussion about the processes of physiology, structure and functionality of the Main City Centre, identification and discussion surrounding the new centers in existing urban area of Cuiabá, and the elaboration of a diagnosis analytic on the spatial distribution of the central areas in the city Cuiabá. The methodological support is based in the analysis of socio-spatial process variables, form, function and structure present and active in the fields of study chosen. The results point towards: an outline history of the centralization process and an analysis of the current socioeconomic situation of the Main Center; saving relationship with relevant decentralization process in Cuiabá, driven by rapid urban growth of the city from the 1970s, and the consequent emergence of new and significant areas that go to play central role in new areas concentrating flows in the inner city. Also appear as a search result the identification and characterization of different centralities intraurbanas arranged in urban areas, which were classified in this work as Expanded Center, Axes Splitting the Main Center, Specialized Areas, Traditional sub-centers and shopping malls. Thereafter, in this study, are now considered as a Center Expanded area surrounding the Main Center, which along with this form the Central Area of the city, the axes correspond Splits Center Main avenues Fernando Corrêa da Costa, Miguel Sutil and Historiador Rubens de Mendonça; Specialized Areas, characterized by the Centro Politico Administrativo de Cuiabá (CPA), the Industrial Distrito Integrado Industrial e Comercial de Cuiabá (DIICC), Carmindo de Campos Avenue and the Avenue das Flores; Traditional correspond to the sub-centers around the main streets of the neighborhoods Morada da Serra, Pedra 90 and Tijucal, and shopping malls, centralities in its conception, represented by the mall's Goiabeiras, 3 Américas and Pantanal, and their surrounding areas. In this perspective, the studies point towards an important decentralization process in Cuiabá, driven by the dynamics of capital in the production of urban space.